Perancangan Alat Pemotong Kue Yangko dengan Metode Rasional - Anwar, M. Khoirul; Jazuli, Jazuli; Setyaningrum, Ratih (Universitas Dian Nuswantoro, 2017)
Yangko cake is a culinary area that is often used as souvenirs when visiting the city of Yogyakarta with a sticky texture, supple and soft. In yangko cake making, producers are faced with problems during the process of cutting the cake. It is necessary to have an effective cake cutter so that it can increase its productivity. From the results of research conducted by using rational methods, obtained the result that the cutting tool cake is designed by using sling cutting technology. The rational method consist of several stages: (1) clarifying objectives, (2) establish function, (3) setting requirement, (4) determining characteristic, (5) generating alternatives, (6) evaluating alternatives, dan (7) product improvements. From the results of experimental tools that have been done, obtained increased time efficiency and productivity cutting process as much as 60%. In addition, the cuts using this tool also have better quality than before and reducing the number of defective products. In terms of use, this tool has a good enough resistance and is designed with the concept of ergonomics so it can be used with comfort.